Fetal autonomic malfunction as a marker of fetal distress in growth-restricted fetuses: three case reports - Igor Victorovich Lakhno; Schmidt Alexander (Korean Society of Obstetrics and Gynecology, 2019)
Fetal growth restriction (FGR) is characterized by fetal compromise and delayed neurological maturation. We report 3 cases of early FGR in the 26th week of gestation, based on hemodynamic Doppler monitoring, conventional cardiotocography, and non-invasive fetal electrocardiography (NI-FECG). Fetal heart rate variability (HRV), beat-to-beat variations, and fetal autonomic brain age scores (fABASs) were normal despite the absence of umbilical diastolic flow in the first case and the pregnancy continued to 30 weeks. NI-FECG helped achieve better fetal maturity. Fetal HRV and fABASs were low in the second and third cases. Fetal demise occurred soon in both cases. We conclude that NI-FECG could be a prospective method for the detection of fetal distress in early FGR.